2008
DOI: 10.1124/mol.108.051078
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of an Agonist Determines Coupling Preference of β2-Adrenoceptor to Different G Proteins in Cardiomyocytes

Abstract: A fundamental question regarding receptor-G protein interaction is whether different agonists can lead a receptor to different intracellular signaling pathways. Our previous studies have demonstrated that although most ␤ 2 -adrenoceptor agonists activate both G s and G i proteins, fenoterol, a full agonist of ␤ 2 -adrenoceptor, selectively activates G s protein. Fenoterol contains two chiral centers and may exist as four stereoisomers. We have synthesized a series of stereoisomers of fenoterol and its derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
86
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 40 publications
6
86
1
Order By: Relevance
“…There may be a steric effect of the ␣-ethyl group that compromises receptor conformational changes linked to G protein activation, without affecting receptor phosphorylation or arrestin binding. In cardiac myocytes, the S,R-isomer of fenoterol stimulates substantially higher activation of G␣ i2 than the R,R-isomer, whereas (R,R)-fenoterol produces higher activation of G␣s than (S,R)-fenoterol (Woo et al, 2009). This differential G s /G i coupling is apparent in functional assays including myocyte contractility and Erk1/2 phosphorylation, and the authors suggest that agonists selectively able to stimulate ␤ 2 -AR Gs coupling, without stimulating ␤ 2 -AR G i coupling or ␤ 1 -AR activation, may have considerable therapeutic benefit.…”
Section: Introductionmentioning
confidence: 91%
“…There may be a steric effect of the ␣-ethyl group that compromises receptor conformational changes linked to G protein activation, without affecting receptor phosphorylation or arrestin binding. In cardiac myocytes, the S,R-isomer of fenoterol stimulates substantially higher activation of G␣ i2 than the R,R-isomer, whereas (R,R)-fenoterol produces higher activation of G␣s than (S,R)-fenoterol (Woo et al, 2009). This differential G s /G i coupling is apparent in functional assays including myocyte contractility and Erk1/2 phosphorylation, and the authors suggest that agonists selectively able to stimulate ␤ 2 -AR Gs coupling, without stimulating ␤ 2 -AR G i coupling or ␤ 1 -AR activation, may have considerable therapeutic benefit.…”
Section: Introductionmentioning
confidence: 91%
“…The basis for the ligand-specific differences in pharmacological outcome lies in the interplay between the molecular structure of the agonist (Kahsai et al, 2011) and the cellular environment of the receptor. In the first instance, we have shown that the G s /G i selectivity of Fen is a function of molecular structure and stereochemistry, because Fen preferentially activated G S signaling in a cardiomyocyte contractility model, whereas (S,RЈ)-fenoterol and MNF activated both G S and G i proteins (Woo et al, 2009;Jozwiak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a seminal study, Michel Bouvier's group showed that the pharmacological profile of the β 1 AR with regard to cAMP accumulation is quite different from the profile with respect to the activation of extracellular signal-regulated kinase (ERK) pathways (Galandrin et al 2008). Similarly, the pharmacological profile of the recombinant β 2 AR with respect to coupling to G i and G s proteins in insect cell membranes is different (Wenzel-Seifert and Seifert 2000), and certain stereoisomers of β 2 AR ligands differ in their capacity to direct β 2 AR signaling towards G i versus G s proteins (Woo et al 2009;Seifert and Dove 2009). Coupling of a given GPCR to a specific G protein is not only influenced by the ligand bound to the receptor but also by the expression level of the receptor, the concentration of the G protein in the vicinity of the receptor, and the particular cell type examined (Kenakin 2007(Kenakin , 2009Schneider and Seifert 2010).…”
mentioning
confidence: 99%
“…Accordingly, the role of G iα2 must be studied in greater detail. Moreover, ligand-specific β 2 AR coupling to G i and G s proteins has been observed in cardiomyocytes (Woo et al 2009). Furthermore, several therapeutically relevant βAR antagonists clinically used for the treatment of cardiovascular diseases including chronic heart failure, hypertension, and coronary heart disease constitute, in fact, not simple antagonists but rather ligands exhibiting biased signaling (Galandrin et al 2008;Rajagopal et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation